2002
DOI: 10.1177/00238309020450020101
|View full text |Cite
|
Sign up to set email alerts
|

Informative Prosodic Boundaries

Abstract: In principle, a prosodic boundary in an utterance might affect its interpretation in a local, context-independent fashion. In a right-branching language like English, the presence of a large prosodic boundary might signal the end of the current constituent, requiring the following constituent to be attached high in the syntactic tree. We present three listening experiments that test an alternative position suggested in Carlson, Clifton, and Frazier (2001) as the "informative boundary" hypothesis. This hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
126
3
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 19 publications
10
126
3
2
Order By: Relevance
“…Other theories focus on a more limited range of phenomena and characterize the mapping within this domain. One commonly explored phenomenon is the prosodic phrasing of syntactic attachment ambiguities (Schafer, 1997;Carlson et al, 2001;Clifton, Carlson & Frazier, 2002). There are several reasons why this might be a particularly productive place to begin pinning down the syntax-prosody interface.…”
Section: Authors' Notementioning
confidence: 99%
See 3 more Smart Citations
“…Other theories focus on a more limited range of phenomena and characterize the mapping within this domain. One commonly explored phenomenon is the prosodic phrasing of syntactic attachment ambiguities (Schafer, 1997;Carlson et al, 2001;Clifton, Carlson & Frazier, 2002). There are several reasons why this might be a particularly productive place to begin pinning down the syntax-prosody interface.…”
Section: Authors' Notementioning
confidence: 99%
“…More recently, however, other theorists have suggested that the boundary before the ambiguous phrase can only be interpreted in light of the global prosodic structure of the utterance (Schafer, 1997;Clifton et al 2002;Carlson et al, 2001). This claim is made most explicit in the work of Carlson, Clifton and Frazier who argue that the boundary at location B is always interpreted with respect to any other boundary that occurs before a constituent that contains the lower attachment site but not the higher attachment site (Clifton et al, 2002).…”
Section: Authors' Notementioning
confidence: 99%
See 2 more Smart Citations
“…Conversation would be impossible if efficient mechanisms for dealing with uhs, ums, repeats and repairs were not a basic part of the architecture of the human comprehension system. There has been some work examining the influence of PROSODIC 'cues' on comprehension, but even in these approaches the goal is to evaluate the use of prosody during SYNTACTIC operations [4][5][6]. Moreover, studies of prosody have not considered utterances containing mistakes and misarticulations, even though they are part of the input the comprehension system routinely processes.…”
mentioning
confidence: 99%